Revolutionizing Tomorrow: The Role of Artificial Intelligence in the Accounting Profession - Vandapuye, Sophia; Jabraoui , Siham (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Given the increasingly sophisticated technological advancements that are reshaping our current work environment, it is crucial to acknowledge that the concept of artificial intelligence represents a fundamental lever in the development process of the accounting profession, which accountants must integrate. This profession is undergoing significant transformation, as tasks once thought to be exclusive to humans are now being performed by machines. By incorporating artificial intelligence, the accounting profession would experience an evolution through the involvement of robots and machines within their firms, simplifying many tasks and enabling professionals to focus on high-value-added activities. Accountants are developing professional profiles through complex systems based on artificial intelligence, aiming to enhance the skills and performance of their employees while remaining competitive. To achieve this, employees must be ready to adapt and acquire training to effectively embrace and navigate this digital revolution. In line with this objective, this research paper aims to analyze the implication of integrating artificial intelligence on the accounting profession. To accomplish this, the study relies primarily on existing theories and includes a qualitative investigation through semi-structured interviews conducted with 20 accounting firms operating in different cities across Morocco